2019
DOI: 10.3390/ijerph16162828
|View full text |Cite
|
Sign up to set email alerts
|

Association of Environmental Features and the Risk of Alzheimer’s Dementia in Older Adults: A Nationwide Longitudinal Case-Control Study

Abstract: Little is known about the association between environmental features and the risk of Alzheimer’s dementia (AD). This study aims to investigate the association of physical and social environments with the incidence of AD. We identified 12,401 newly diagnosed AD cases aged ≥65 years in 2010, with the same no. of matched controls from National Health Insurance claims in Taiwan. Environmental data were collected from government statistics including three physical environments and three social environments. Multile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
(78 reference statements)
0
21
0
2
Order By: Relevance
“…The most common demographic data measure was neighborhood socioeconomic status, using either single indicators (e.g., median income; n = 8), or indices of area deprivation (n = 19). Other demographic data measures included income inequality calculated at the U.S. state or metropolitan statistical area [ 114 , 125 ]; racial/ethnic residential composition [ 116 ]; and the density of older adults living alone [ 120 ]. Six studies aggregated study participant responses to define area-level social activity participation [ 80 ] and social support/cohesion [ 50 , 68 , 123 , 124 , 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most common demographic data measure was neighborhood socioeconomic status, using either single indicators (e.g., median income; n = 8), or indices of area deprivation (n = 19). Other demographic data measures included income inequality calculated at the U.S. state or metropolitan statistical area [ 114 , 125 ]; racial/ethnic residential composition [ 116 ]; and the density of older adults living alone [ 120 ]. Six studies aggregated study participant responses to define area-level social activity participation [ 80 ] and social support/cohesion [ 50 , 68 , 123 , 124 , 143 ].…”
Section: Resultsmentioning
confidence: 99%
“…The urbanization classification was proposed by Huang et al 18 They categorized all 358 cities and townships of Taiwan into five ordered levels of urbanization based on different indicators, including the number of residents, population density, and the percentage of people working in secondary and tertiary industries. 18,32,33…”
Section: Levels Of Urbanizationmentioning
confidence: 99%
“…However, studies evaluating the effect of green spaces on AD alone have shown contradictory ndings [18][19][20][21]. Moreover, we are not aware of prior studies evaluating the association between green spaces and vascular dementia.…”
Section: Discussionmentioning
confidence: 98%
“…Hypothesized mechanisms include inducing stress restoration, providing opportunities for physical activity and social cohesion, and mitigating environmental hazards [8]. However, the available evidence on the association between green spaces and neurodegenerative diseases among the elderly is mixed and inconclusive, and studies have so far primarily focused on dementia or its precursor, cognitive decline [9,10,[19][20][21][11][12][13][14][15][16][17][18]. As far as we are aware, only one ecological and three longitudinal studies investigated the relationship between exposure to green spaces and neurodegenerative disease mortality: two longitudinal studies reported no association [22,23], while the other two observed a bene cial association [24,25].…”
mentioning
confidence: 99%